Some linguistic suggestions in conducting Malay language classes - Namai, Kenichi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Despite some skeptics, most foreign language teachers, especially those of English as a Foreign Language (EFL)/English as a Second Language (ESL), advocate Communicative Language Teaching (CLT) and have long been conducting student-centered communicative activities in their classrooms. This paper argues that CLT is generally ineffective in teaching quiet students and students with little motivation. In the context of teaching Malay as a foreign language, it introduces an alternative teaching approach that requires teacher-centered drill activities, which have been shown effective in EFL teaching in Japan, a country known for its typically quiet students, most of whom do not see a point in acquiring any practical skills of English. The paper demonstrates the necessity of explaining basic syntactic rules, some of which tend to be taken for granted, that are crucial in helping students of Malay develop a systematic grammar of their target language.